Acyltransferase domain swap in modular type I polyketide synthase to adjust the molecular gluing strength of rapamycin. (7th December 2022) - Pang, Bo; Graziani, Edmund I.; Keasling, Jay D.
Graphical abstract: Abstract: Rapamycin is a molecular glue that forms a ternary complex between the 12 kDa FK506-binding protein (FKBP12) and the mechanistic/mammalian target of rapamycin (mTOR), resulting in the inhibition of the protein kinase activity of mTOR. To probe the effects of partial antagonism at the allosteric binding site at which FKBP12-rapamycin binds to mTOR, analogs of rapamycin were produced with altered binding affinity to mTOR via engineering the rapamycin polyketide synthase (PKS) in its natural producer, S. rapamycinicus ATCC 29253. These efforts resulted in 23‑desmethyl rapamycin, a new rapamycin analog produced via an acyltransferase (AT) swap in module 7 of rapamycin PKS. Surface plasmon resonance analysis indicated that the ternary complex formed from FKBP12, 23‑desmethyl rapamycin, and the FKBP12-rapamycin-binding domain of mTOR (FRB) is more short-lived compared to the rapamycin-derived complex. Also, the new analog showed reduced growth inhibition of Saccharomyces cerevisiae .